2021
DOI: 10.1039/d1sc02918e
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced delayed fluorescence luminogens: the innovation of purely organic emitters for aqueous electrochemiluminescence

Abstract: Due to overcoming the limitation of aggregation caused quenching (ACQ) on solid-state emitter, aggregation-induced emission (AIE) organic luminogens have becoming a promising candidate in aqueous electrochemiluminescence (ECL). However, restricted by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 50 publications
1
68
1
Order By: Relevance
“…Thus, the SOC effect is affected by the molecular surrounding environment, the rigid environment in the solid phase with remarkable intermolecular interactions could facilitate the ISC and RISC processes, this observation is consistent with the mechanism of aggregation induced delayed fluorescence (AIDF). 50–53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the SOC effect is affected by the molecular surrounding environment, the rigid environment in the solid phase with remarkable intermolecular interactions could facilitate the ISC and RISC processes, this observation is consistent with the mechanism of aggregation induced delayed fluorescence (AIDF). 50–53…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the SOC effect is affected by the molecular surrounding environment, the rigid environment in the solid phase with remarkable intermolecular interactions could facilitate the ISC and RISC processes, this observation is consistent with the mechanism of aggregation induced delayed fluorescence (AIDF). [50][51][52][53] 4.3.3 RMSD values and reorganization energy of ISC and RISC processes. As the ISC and RISC processes are not only related to DE ST and the SOC constant, but can also be affected by the reorganization energies, which are related to the geometrical changes.…”
Section: 3mentioning
confidence: 99%
“…The calculation of different photophysical parameters is shown in Table 1 and Table S1,† in which the methods refer to the ever-established TADF photophysical theory. 36,39,44 For the electrochemistry study, the cyclic voltammetry (CV) signals were acquired using a DC1300 Electrochemical workstation (Guangdong Dynechem Electronic Technology Co., Ltd China). Generally, a standard three-electrode system, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, we established the aqueous aggregation-induced delayed fluorescent (AIDF)-ECL, which was effective in eliminating ACQ-induced TADF quenching behavior in aqueous ECL. 36 However, compared with the explored TADF emitters, 30 the qualified AIDF luminogens are scarce since they should simultaneously optimize the AIE and TADF properties in one compound, which is difficult to realize. A universal strategy is thus expected for common TADF emitters towards efficient and stable aqueous TADF-ECL.…”
Section: Introductionmentioning
confidence: 99%
“…20 Tang's group reported that aggregation-induced delayed fluorescent (AIDF) luminogens extremely boosted the aqueous ECL efficiency 5.4 times by overcoming the limitation of ACQ. 21 Indeed, the inno-vation of the aggregation-induced emission (AIE) concept provides an ideal platform to solve the ACQ problem. [22][23][24][25][26] Different from the ACQ effect, the fluorescence of AIE luminophores is boosted by aggregate formation, 27,28 which is beneficial for the development of high-efficiency ECL devices.…”
Section: Introductionmentioning
confidence: 99%